Synthesis and characterization of starch and starch derivatives nanoparticles - Aressa, Azman (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study reports a simple, fast, repeatable and cost effective synthesis of starch nanoparticles in microemulsion system. The effects of synthesis conditions on particle size of starch nanoparticle were studied by varying stirring rates, surfactant concentrations, types of oil and series of co-surfactants, phase ratios of oil/co-surfactant and water/oil. Starch nanoparticles with mean particle sizes of 108.60 ± 16.70 nm were synthesized by direct nanoprecipitation method without microemulsion system whereas starch nanoparticles with smaller mean particle size of 82.50 ± 12.40 nm were obtained in microemulsion system. This study showed that the mean particle sizes of starch nanoparticles can be controlled by changing the compositions of microemulsion system. Starch maleate was prepared by reacting maleic anhydride with native sago starch (Metroxylon sagu). Fluorescein isothiocyanate (FITC) was then covalently attached onto starch maleate and fluorescein-labeled starch maleate (FISM) were self-assembled to form nanoparticles upon precipitation into ethanol solution. The mean particle size of these fluorescein-labeled starch maleate nanoparticles was around 87.00 ± 14.30 nm. These fluorescent nanoparticles were strongly fluorescent with an emission wavelength maximum of 518 nm. The fluorescence of these nanoparticles can be quenched by silver (Ag+) and lead (Pb2+) ions. We demonstrated the first use of fluorescent starch maleate nanoparticles as a cheap, effective fluorescent sensing probe for silver and lead ions with detection limits as low as 2.55 x 10-5 M and 3.64 x 10-5 M, respectively.